The Impact Of Sea Sand Mining On The Environment And Economy In Bawean Island - Dewi Rosalina, Maria; Triadi , Irwan; Sumertha KY, I Gede; Widodo, Pujo; Sukendro, Achmed (CV. AFDIFAL MAJU BERKAH, 2024)
This study analyzes the impact of sea sand mining on the environment and local economy in Bawean Island. Located in the Java Sea and part of Gresik Regency, East Java Province, Bawean Island is renowned for its biodiversity and natural beauty. Both legal and illegal sea sand mining have caused various problems, including increased coastal abrasion and erosion, degradation of seawater quality, damage to coral reef ecosystems and mangrove forests, and beach pollution. The economic impacts include a decline in fish catches, reduced tourism appeal, and social conflicts between pro-environment communities and mining parties. The research methodology used is qualitative descriptive, employing literature review for data collection. The findings indicate that sea sand mining results in serious ecosystem damage and adversely affects the economic well-being of local communities. To address these issues, recommended measures include reviewing local regulations, reassessing environmental permits, revoking non-compliant mining licenses, developing alternative economies, planting mangroves, promoting the benefits of mangroves, and adopting an interagency approach. This study emphasizes the importance of sustainable natural resource management and marine ecosystem protection to ensure the well-being of Bawean Island's communities.